2006
DOI: 10.4265/bio.11.17
|View full text |Cite
|
Sign up to set email alerts
|

Sterilization Efficiency of the Photocatalyst against Environmental Microorganisms in a Health Care Facility

Abstract: The photocatalyst equipment consists of a titanium dioxide membrane and an ultraviolet lamp. The authors studied if the photocatalyst equipment is practically useful in sterilizing environmental microorganisms in the health care facility. The number of microorganisms was compared in the cases of no sterilization (control) and the photocatalyst sterilization. As a result, a statistical difference was observed between control and the photocatalyst sterilization against airborne microorganisms (p<0.01), but not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…[141][142][143][144][145] New research is exploring the potential use of nanostructured titanium dioxide photocatalyst materials for sterilizing equipment of environmental microorganisms in the health care facility. 146 Silver nanoparticles are used as antibacterial/antifungal agents in a diverse range of applications: air sanitizer sprays, socks, pillows, slippers, face masks, wet wipes, detergent, soap, shampoo, toothpaste, air filters, coatings of refrigerators, vacuum cleaners, washing machines, food storage containers, cellular phones, and even in liquid condoms.…”
Section: Cosmetics and Other Consumer Products And Health Effectsmentioning
confidence: 99%
“…[141][142][143][144][145] New research is exploring the potential use of nanostructured titanium dioxide photocatalyst materials for sterilizing equipment of environmental microorganisms in the health care facility. 146 Silver nanoparticles are used as antibacterial/antifungal agents in a diverse range of applications: air sanitizer sprays, socks, pillows, slippers, face masks, wet wipes, detergent, soap, shampoo, toothpaste, air filters, coatings of refrigerators, vacuum cleaners, washing machines, food storage containers, cellular phones, and even in liquid condoms.…”
Section: Cosmetics and Other Consumer Products And Health Effectsmentioning
confidence: 99%
“…The UV irradiation effect involved in this sterilization mechanism is presented in Figure la and 1b. The UV irradiation effect on microbicidal activity has been discussed by Shintani et al (2006). BI of G. stearothermophilus ATCC 7953 spores was used to confirm the sterility assurance as it indicated the most resistant species to plasma sterilization (Tamazawa, 2004;Kelly-Wintenberg et al, 1998).…”
Section: Microbicidal Activitymentioning
confidence: 99%
“…Several studies have demonstrated that some of these microorganisms are resistant to antibiotics such as MRSA and VRE and so on http //www.betterhealth. vic.gov.au/bhcv2/bhcarticles.nsf/pages/Antibiotic_resis-ta nt_bacteria and have an impact on the patients Elixhauser and Steiner, 2007 this indicates the need for improved sterilization procedures to ensure medical products are free from bioburden, airborne falling microorganisms or adhesive microorganisms as far as possible Shintani et al, 2003Shintani et al, 2006Shintani, 2013Shintani, 2014 . However, some studies Lipscomb et al, 2006Lipscomb et al, , 2008 have shown that significant quantities of residues composed of salts, proteins and organic matter are left on surgical instruments even after complete cleaning and sterilization in sterile service departments SSDs .…”
Section: Introductionmentioning
confidence: 99%